Caracterização microestrutural de propriedades viscoelásticas de ligantes asfálticos usando a microscopia de força atômica - Macedo, Thaísa Ferreira (2018)
This research aims to evaluate the mechanical properties of each microstructural an asphalt binder component by means of nanoindentation creep compliance tests in an atomic force microscope (AFM). During the indentation tests, different load magnitudes were applied to each binder constituent in different aging conditions to identify the limits of linearity for their viscoelastic behavior. Two indentation methodologies were evaluated and the most optimized was selected to obtain creep compliance of the binder constituents. A statistical analysis procedure was proposed to overcome some challenges related to the determination of representative contact area between the nanoindenter tip and the asphalt binder. This information was relevant for the calculation of the creep compliance from the deformation histories. The linear viscoelastic component properties were used as input parameters in numerical microstructural simulations and the results were compared with monotonically load tests. The good match between the results indicate that the component viscoelastic properties were properly obtained by the methodology proposed in the research.